Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have trouble understanding why, when finding the limit of a recurrently defined sequence, we can assume that $x_n=x_{n+1}$ to find the actual limit.

I figured it's got something to do with the fact that $\lim\limits_{n \to \infty} x_n=\lim\limits_{n \to \infty} x_{n+1}$ and intuitively that makes perfect sense, but it's the theory behind it that evades my understanding (we can't just say that "because $|x_n-x_{n+1}|$ for high enough $n$ is very close to zero, we might aswell make them equal", right?)

Example: In $x_1=0$ , $ x_{n+1}=\frac{1}{1+x_n}$ I'd use the equality $ L=\frac{1}{1+L}$

This question probably isn't very well formulated, but that comes from my lack of understanding of the problem, sorry! (and thanks for the answer :)

share|cite|improve this question
up vote 4 down vote accepted

We don't really assume that $x_n=x_{n+1}$. Instead, suppose that the limit exists, call it $x$. Then $\lim_{n\to\infty}x_n=x$. This, by definition of limit, means that for every $\epsilon>0$ there is a $N\in\mathbb N$ such that for all $n>N$ we have $|x_n-x|<\epsilon$. Intuitively, for every $\epsilon>0$, the sequence is $\epsilon$-close to $x$ from some place on.

Now, we will show that it follows that $\lim_{n\to\infty}x_{n+1}=x$. Let $\epsilon>0$. Then for $n>N$ we have $n+1>N$ and therefore by the previous paragraph, $|x_{n+1}-x|<\epsilon$. So, for all $n>N$, the inequality $|x_{n+1}-x|<\epsilon$ holds. This means that for every $\epsilon>0$, the number $x_{n+1}$ is also $\epsilon$-close to $x$ for all $n>N$, i.e. the limit exists and is equal to $x$.

Similarly, we can show that if $\lim_{n\to\infty}x_{n+1}=x$, then $\lim_{n\to\infty}x_n=x$. To see this, just write out what $\lim_{n\to\infty}x_{n+1}=x$ means in terms of $\epsilon$, $N$ and $n$. Then you will be able to show that $x_n$ is $\epsilon$-close to $x$ for all $n>N+1$.

What all this means is that $\lim_{n\to\infty}x_n=x$ holds precisely if $\lim_{n\to\infty}x_{n+1}=x$ holds, i.e. the conditions are equivalent.

share|cite|improve this answer
Perfect, thanks a lot! – Dahn Jahn Nov 11 '12 at 13:09
So, if $\lim_{n \to \infty}(u_{n} -u_{n+2}) = 0$, then $\lim_{n \to \infty}(u_{n} -u_{n+1}) = 0$? – nameless Jul 11 at 14:32
@nameless: that's true, if you assume for instance that $\lim_{n\to\infty}u_n$ exists. Otherwise, $u_n=(-1)^n$ is a counterexample. – Dejan Govc Jul 11 at 16:03
@DejanGovc Thanks for your reply. Please check for the proof. We assume that $\lim_{n} u_{n}$ exists, namely, $L \in \mathbb{R}$. Let $\epsilon > 0$. By our assumption, there exists natural number $K$ such that for each $n \geq K$, we have $|u_{n} - L| < \frac{\epsilon}{2}$. Then $|u_{n} - u_{n+1}| \leq |u_{n} - L| + |u_{n+1} - L| < \epsilon$. Is this correct? If it is correct, when we use the condition $\lim_{n \to \infty}(u_{n} -u_{n+2}) = 0$? – nameless Jul 15 at 17:11
@nameless: looks good to me. You don't have to use $\lim_{n \to \infty}(u_{n} -u_{n+2}) = 0$. If the limit exists, $\lim_{n \to \infty}(u_{n} -u_{n+1}) = 0$ and $\lim_{n \to \infty}(u_{n} -u_{n+2}) = 0$ are automatically true. (In particular, they imply each other.) – Dejan Govc Jul 15 at 17:24

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.